L-F001, a Multifunctional Fasudil-Lipoic Acid Dimer Prevents RSL3-Induced Ferroptosis via Maintaining Iron Homeostasis and Inhibiting JNK in HT22 Cells - Peng, Weijia; Ouyang, Ying; Wang, Shuyi; Hou, Jiawei; Zhu, Zeyu; Yang, Yang; Zhou, Ruiyu; Pi, Rongbiao (Frontiers in Cellular Neuroscience, 2022)
Ferroptosis, an iron-dependent form of non-apoptotic cell death, plays important roles in cerebral ischemia. Previously we have found that L-F001, a novel fasudil-lipoic acid dimer with good pharmacokinetic characters has good neuroprotection against toxin-induced cell death in vitro and in vivo. Here, we investigated the protective effects of L-F001 against a Glutathione peroxidase 4 (GPX4) inhibitor Ras-selective lethality 3 (RSL3) -induced ferroptosis in HT22 cells. We performed MTT, Transmission Electron Microscope (TEM), Western blot, and immunofluorescence analyses to determine the protective effects of L-F001 treatment. RSL3 treatment significantly reduced HT22 cell viability and L-F001 significantly protected RSL3-induced cell death in a concentration-dependent manner and significantly attenuated Mitochondrial shrinkage observed by TEM. Meanwhile, L-F001 significantly decreased RSL3-induced ROS and lipid peroxidation levels in HT22 cells. Moreover L-F001could restore GPX4 and glutamate-cysteine ligase modifier subunit (GCLM) levels, and significantly deceased Cyclooxygenase (COX-2) levels to rescue the lipid peroxidation imbalance. In addition, FerroOrange fluorescent probe and Western blot analysis revealed that L-F001 treatment decreased the total number of intracellular Fe2+ and restore Ferritin heavy chain 1 (FTH1) level in RSL3-induced HT22 cells. Finally, L-F001 could reduce RSL3-induced c-Jun N-terminal kinase (JNK) activation, which might be a potential drug target for LF-001. Considering that L-F001 has a good anti-ferroptosis effect, our results showed that L-F001 might be a multi-target agent for the therapy of ferroptosis-related diseases, such as cerebral ischemia.